Leptin, malnutrition, and immune response in rural Gambian children. Issue 3 (1st September 2002) - Moore, S E; Morgan, G; Collinson, A C; Swain, J A; O'Connell, M A; Prentice, A M
Abstract : Background: The adipocyte derived hormone, leptin, has cytokine like function and may mediate the effects of starvation on immunity. Mice with congenital leptin deficiency ( ob/ob ) have small hypocellular thymuses and impaired cellular immunity. In humans leptin influences the differentiation of naïve and memory cells in vitro, and genetic leptin deficiency has been associated with an ill defined susceptibility to infection. Aims: To describe the in vivo relation of leptin and immune function in children. Methods: Fasting plasma leptin concentrations, immune function (T and B cell mediated vaccine responses and delayed type hypersensitivity), and mucosal function (dual sugar permeability test and salivary sIgA concentrations) were measured in a cohort of 472 moderately undernourished rural Gambian children. Results: Leptin concentrations correlated with body fat assessed by mid upper arm circumference or BMI for age Z scores, and were very low compared to well nourished European norms (males 1.8 v 11.1 ng/ml; females 2.4 v 13.8 ng/ml). No detectable relations were found between leptin concentrations and any of the measures of immune or mucosal function. Conclusions: The data confirm that leptin acts as a peripheral signal of energy restriction, but do not support an association between fasting plasma leptin levels and immune function in children of this age.